The role of tumor angiogenesis as a therapeutic target in colorectal cancer. Issue 3 (4th March 2018) - Battaglin, Francesca; Puccini, Alberto; Intini, Rossana; Schirripa, Marta; Ferro, Alessandra; Bergamo, Francesca; Lonardi, Sara; Zagonel, Vittorina; Lenz, Heinz-Josef; Loupakis, Fotios
ABSTRACT: Introduction : Angiogenesis is a complex process regulated by several pro- and anti-angiogenic factors, thus the loss of its fine equilibrium plays a key role in colorectal cancer (CRC) development and progression. Therapeutic agents targeting VEGF/VEGFR signaling, the main regulator of this process, proved to be effective across different treatment lines in metastatic CRC (mCRC) and contributed greatly to improve patients' survival in recent years. Areas covered : This review aimed to summarize the actual body of knowledge available on the VEGF pathway in CRC, including currently available anti-angiogenic drugs and treatment challenges, mechanisms of resistance, promising predictive biomarkers and future perspectives. Expert commentary : Angiogenesis inhibition in subsequent lines of treatment is a valid strategy in the continuum of care of mCRC patients. In this scenario, the availability of multiple agents warrants to tailor therapy to an individualized approach. However, the validation of predictive biomarkers to aid therapeutic decisions remains an issue. Intrinsic and adaptive resistance to anti-angiogenic agents comprises distinct and intertwined processes, eventually leading to treatment failure and disease progression. The expanding knowledge on the mechanisms underlying the angiogenesis pathway, different potential treatment targets and mechanisms of tumor resistance, may lead to promising new perspectives in this field.